Credit Policy for Agricultural and Rural Development in Vietnam - The Current Situation Period 2015-2025, and Some Recommendations - Dao, Vu Thi (Archives of Business Research, 2025)
Credit policy for agriculture and rural areas plays a pivotal role in the sustainable development of Vietnam’s economy. The period 2015–2025 marks a transitional phase toward agricultural modernization and rural development. Although the government has introduced numerous mechanisms and policies to enhance credit accessibility, limitations remain, such as low levels of unsecured lending, repayment difficulties and high risk, limitations in entrusted lending channels, complex policy system. This research analyzes the status of agricultural and rural credit policies in Vietnam from 2015 to 2025 and proposes solutions to improve these policies for the future.